Kefir: A new role as nutraceuticals - Setyowati, Hanny; setyani, Wahyuning (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2016)
Nutraceutical is the fusion of nutrition and pharmaceutical. This products, in broad, are food or part of food that provides medical or health benefits including the prevention and or treatment of a disease. Kefir is renowned nutraceutical dairy products produced through fermentation of bacteria and yeasts and naturally present in grains of kefir. The nutritional attributes are due to presence of vital nutrients such as carbohydrates, amino acids, proteins, minerals, phosphorus, vitamin, calcium, and certain biogenic compounds. Intestinal immunity, antimicrobial, anticarcinogenic, hypocholesterolemic effect, antibiabetic, effect on blood pressure level, antioxidant, wound healing, and lactose intoleran can be achieved using this products. The purpose of this review is to gather information about composition, methods of production, and therapeutic properties of kefir products to provide justification for its consumption. This review confirms that kefir can be a new role of nutraceutical products.